A Proposed Functional Abilities Classification Tool for Developmental Disorders Affecting Learning and Behaviour - Klein, Benjamin; Kraus de Camargo, Olaf (Frontiers in Education, 2018)
Children with developmental disorders affecting learning and behaviour (e.g. attention, social communication, language and learning disabilities etc.) require individualized support across multiple environments to promote participation, quality of life and developmental outcomes. Support to enhance participation is based largely on individual profiles of functioning (e.g. communication, cognitive, social skills, executive functioning etc.), which are highly heterogeneous within medical diagnoses. Currently educators, clinicians and parents encounter widespread difficulties in meeting children’s needs as there is lack of universal classification of functioning and disability for use in school environments. Objective: A practical tool for functional classification broadly applicable for children with developmental disorders affecting learning and behaviour could facilitate the collaboration, identification of points of entry of support, individual program planning and reassessment in a transparent, equitable process based on functional need and context. We propose such a tool, the Functional Abilities Classification Tool (FACT) based on the concepts of the ICF (International Classification of Functioning, Disability and Health). FACT is intended to provide ability and participation classification that is complementary to medical diagnosis. For children presenting with difficulties, the proposed tool initially classifies participation over several environments. Then, functional abilities are classified and personal factors and environment are described. Points of entry for support are identified given an analysis of functional ability profile, personal factors, environmental features and pattern of participation. Conclusion: Case examples, use of the tool and implications for children, agencies and the system are described.